Influence of time conditions on the soil temperature indicators in Kazakhstan - Maira Kussainova; Maxat Toishimanov1; Anel Syzdyk; Timur Tamenov; Nursultan Nurgali; Jiquan Chen (Caspian Journal of Environmental Sciences)
Interest in studying the influence of the conditions of the year and time of day on the soil temperature indicators has been increasing in recent years to develop new adaptive strategies in agriculture and provide scientific substantiation for making decisions on the sustainable use and protection of natural resources. No research in this direction has been conducted in Kazakhstan to date. The presented studies were carried out in 2021-2023 in the dry network of the Ili Alatau in the Almaty region. The soil temperature was measured at 10 cm depth with CS107 thermocouples, and the average temperature was recorded every hour using the CR-10 datalogger. The data analysis was carried out using RStudio. The purpose of this study was to analyze the influence some factors such as the year, month, and time of day on the soil temperature indicators. It was found that the year, month, and time of day have a significant impact on the indicators of the variable temperature. This indicator amounted to -1.6, 7.5, and -5.2 °С in 2021, 2022, and 2023, respectively. The soil temperature warmed up most significantly between 12 PM and 6 PM (8.6-17.3 °С). The average soil temperature by 9 PM, 12 AM, 3 AM, 6 AM, and 9 AM decreased to 3.8, -0.6, 2.9, -4.0, and -2.9 °С, respectively. The average monthly temperature indicators were 4.3-8.3 °C in March and October. They were higher in April and September (11.7-14.6 °С). They were the highest in June, July, August, and September (20.3-25.8 °С). The results of the study are of fundamental importance for developing new adaptive strategies in agriculture and providing scientific substantiation for making decisions on the sustainable use and protection of natural resources.